1988
DOI: 10.1677/joe.0.1180375
|View full text |Cite
|
Sign up to set email alerts
|

Adrenal glands alter the concentration of oestradiol-17β and its receptor in the uterus of ovariectomized ewes

Abstract: To investigate the effects of adrenal hormones on oestrogen activity in the uterus, ovariectomized ewes were either adrenalectomized, administered glucocorticoid-like preparations (CORT), or remained as controls. The adrenalectomized ewes were maintained with a corticoid-replacement therapy and monitored daily for plasma glucose and Na+/K+ concentrations. Blood samples were collected from all ewes at 15-min intervals for 4 h and assayed for LH and FSH. The adrenalectomized ewes were killed 9 days after adrenal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

1989
1989
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 12 publications
1
11
0
Order By: Relevance
“…The Bo was 47%, the NSB was 3.6%, the minimal detectable concentration was 0.08 ng/ml and the ED50 was 3.84 ng/ml. Plasma cortisol were analysed using the method of Atkinson and Adams (1988). All samples were measured in a single assay.…”
Section: Analysesmentioning
confidence: 99%
“…The Bo was 47%, the NSB was 3.6%, the minimal detectable concentration was 0.08 ng/ml and the ED50 was 3.84 ng/ml. Plasma cortisol were analysed using the method of Atkinson and Adams (1988). All samples were measured in a single assay.…”
Section: Analysesmentioning
confidence: 99%
“…Samples were assayed for FSH using a double-antibody radioimmunoassay provided by the pituitary agency of NIH and validated in our laboratory (Atkinson & Adams, 1988). Preparations NIAMDD-oFSH-RP-1 and NIAMDD-oFSH-I-1 were used for reference and iodination, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…This pathway was confirmed to be the one by which effects of acute treatment with glucocorticoids occur (Campbell 1978, Atkinson & Adams 1988, Rabin et al 1990. Acute treatment with glucocorticoids has been shown to greatly diminish oestrogenstimulated proliferative activity as well as the number of oestrogen receptors in all the uterine cell types (Atkinson & Adams 1988, Rabin et al 1990, Bigsby 1993). The present work also demonstrates a decrease in proliferation in the luminal and glandular epithelia, where the number of glucocorticoid receptors may also be reduced.…”
Section: Discussionmentioning
confidence: 76%
“…Almost all investigations of this process have clearly shown that glucocorticoids greatly diminish oestrogen-stimulated synthesis of DNA and activation of proliferation in the uterus (Tchernitchin et al 1975, Campbell 1978, Stewart et al 1983, Bigsby 1993. Moreover, the content of various factors and activity of various processes, such as ornithine decarboxylase activity (Stewart et al 1983), number of oestrogen receptors (Lisk & Reuter 1976, Markaverich et al 1981, Atkinson & Adams 1988, Rabin et al 1990, Zamorano et al 1992, blood flow (Monheit & Resnik 1981), protein synthesis (Lippe & Szego 1965, Sullivan et al 1983, prostaglandin synthesis (Dey et al 1982, Pakrasi et al 1983, Jacobs et al 1994), c-fos mRNA (Kirkland et al 1992), insulin-like growth factor-I mRNA (Sahlin 1995), associated or mediated oestradiol-induced increase in mitotic activity in the uterus, are also inhibited by glucocorticoids. However, it should be noted that all the researches so far have only demonstrated glucocorticoid action after acute or shortterm treatment, and there are no data on long-term effects of glucocorticoids on oestradiol-induced processes in the uterus.…”
Section: Introductionmentioning
confidence: 99%